Literature Review: Risk Factors Affecting the Incidence of Malaria Infectious Disease and Preventive Measures in Indonesia. - Salsabilla, Diva Rizqi; Hilmi, Indah Laily; Salman, Salman (Jurnal EduHealth, 2022)
Some areas in Indonesia are still endemic areas for malaria, including Papua, Maluku, Nusa Tenggara, Sulawesi, Kalimantan and the island of Sumatra such as Bengkulu and Riau. Malaria is still a major cause of morbidity and mortality in Indonesia. Based on data from the total number of malaria cases in 2019, there were 250,644 cases, and the highest case of around 86% occurred in Papua with a total of 216,380 cases occurring. Malaria is an infectious disease caused by the Plasmodium parasite contained in the female Anopheles mosquito. The Anopheles mosquito can spread because it is influenced by several factors, namely the environment, knowledge and attitude factors, behavioral factors and others. The purpose of this study was to analyze the risk factors for malaria and its prevention measures in Indonesia. The method used is a literature review, by searching for reference literature using Google Scholar, and Research Gate. Literature articles used in the last five years (2017-2022). The results of this study indicate that the dominant risk factors for malaria transmission are the use of mosquito nets, the use of mosquito repellent, the habit of being outside the house at night, and malaria prevention measures.